Pengaruh Pengalaman Kerja, Motivasi, dan Kemampuan Kerja terhadap Kinerja Karyawan PT. PLN (Persero) di Kecamatan Sekayu Kabupaten Musi Banyuasin - Florinda Putri Feriana; Ivala Khoiril Mala (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
In 2017 employee performance has not reached the target due to lack of work experience, motivation and a work environment that is less supportive of employee performance, but in the following year the realization of employee performance began to increase due to the influence of work experience, the form of motivation provided by the company to employees and a directed and more conducive work environment. So that in 2018 to 2021 there was an increase in employee performance due to the influence of work experience, motivation and a good work environment. The purpose of this study was to analyze the effect of work experience, motivation, and work environment on the performance of employees of PT PLN (Persero) in Sekayu District, Musi Banyuasin Regency. The research used is descriptive qualitative. Data collection techniques using observation, interviews and documentation. The technique of analyzing the data is reduction, presentation and conclusion. The results of descriptive analysis show that work experience affects employee performance in doing their work, motivation has an influence on improving employee performance, work ability overcomes good ability to work and employee performance can be improved both good and bad.